2014
DOI: 10.1002/ccd.25733
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk factors of re‐intervention after endovascular repair for type B aortic dissections

Abstract: we concluded that chronic phase, smoking and too big oversizing were potential risk factors of re-intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Among the remaining citations, 32 were excluded for the following reasons: 6 were reviews or invited commentaries, 17 were single‐case reports, 3 were TEVAR or hybrid repair only for type A aortic dissection, and 6 studies were lack of outcomes of interest (Figure ). Therefore, 50 studies were included in the meta‐analysis with a total of 8969 patients …”
Section: Resultsmentioning
confidence: 99%
“…Among the remaining citations, 32 were excluded for the following reasons: 6 were reviews or invited commentaries, 17 were single‐case reports, 3 were TEVAR or hybrid repair only for type A aortic dissection, and 6 studies were lack of outcomes of interest (Figure ). Therefore, 50 studies were included in the meta‐analysis with a total of 8969 patients …”
Section: Resultsmentioning
confidence: 99%
“…133 Reintervention rates for TEVAR following TBAD remain high and seem mainly associated with excessive oversizing, bare spring stent-grafting in the proximal landing zone, large aortic dilatation, and anticoagulant therapy. 86,134 Marfan disease, smoking, and type I endoleak are the main predictors. 134,135 High conversion rates to open surgical repair are reported (8%-14%), mainly due to retrograde AD.…”
Section: Rare Complicationsmentioning
confidence: 99%
“…16 Sze et al followed up patient who underwent TEVAR for aortic dissection and found that 59% of them had endoleak, and they found coverage of the left subclavian artery, small radius of aortic arch curvature and greatest length of unapposed proximal stent-graft were associated with endoleak. 17 And as we previous reported 18 and as Mestres et al reviewed, 19 re-interventions after TEVAR are mostly related to endoleaks. In our experience, it should be deal with aggressively if type I endoleak visualized early and fast after aorta visualized in aortography after stent-grafts deployment.…”
Section: Discussionmentioning
confidence: 73%